Effect of Different Types of Ketogenic Diet on Lipid Profile, Atherogenic Ratios, and Cardiac Histopathology in Male Albino Rats (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2026)
Background and Objective: Dyslipidemia, characterized by abnormal levels of total cholesterol (TC), low-density lipoprotein (LDL-C), high-density lipoprotein (HDL-C), and triglycerides (TG), is a major risk factor for cardiovascular diseases. Although the ketogenic diet (KD) is widely used as a very low-carbohydrate, high-fat therapeutic approach, its effects on lipid metabolism and cardiac health remain controversial. This study aimed to compare the impact of different types of ketogenic diets on serum lipid profile, atherogenic ratios, and cardiac histopathological changes in male albino rats.Methods: Thirty-five male albino rats were randomly divided into five groups of seven: a control group, a high-fat  ketogenic diet (70% coconut oil), a high-fat ketogenic diet (70% animal fat), a high-protein ketogenic diet (35% casein, 60% coconut oil), and a cyclical ketogenic diet (70% coconut oil). The dietary intervention lasted for 50 days. At the end of the intervention, serum lipid parameters (TC, TG, LDL-C, HDL-C) and lipid ratios (TC/HDL-C, TG/HDL-C, LDL-C/HDL-C) were measured. Also, histopathological examination of heart tissue was performed using hematoxylin-eosin (H&E) staining. SPSS25 software was used for statistical analysis (p